2010
DOI: 10.1074/jbc.m109.058503
|View full text |Cite|
|
Sign up to set email alerts
|

Nickel Ions Inhibit Histone Demethylase JMJD1A and DNA Repair Enzyme ABH2 by Replacing the Ferrous Iron in the Catalytic Centers

Abstract: Iron-and 2-oxoglutarate-dependent dioxygenases are a diverse family of non-heme iron enzymes that catalyze various important oxidations in cells. A key structural motif of these dioxygenases is a facial triad of 2-histidines-1-carboxylate that coordinates the Fe(II) at the catalytic site. Using histone demethylase JMJD1A and DNA repair enzyme ABH2 as examples, we show that this family of dioxygenases is highly sensitive to inhibition by carcinogenic nickel ions. We find that, with iron, the 50% inhibitory conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 51 publications
1
67
0
Order By: Relevance
“…Cobalt compounds or nickel compounds can alter the histone modification [27].They can affect the activity of histone demethylase such as inhibiting function of nickel ions on JMJD1A by replacing the ferrous iron in the catalytic centers [28]. Chronic exposure to nickel compounds has been connected to the increased risks of cancer, and alteration of histone modification may be one important factor [29].…”
Section: Discussionmentioning
confidence: 99%
“…Cobalt compounds or nickel compounds can alter the histone modification [27].They can affect the activity of histone demethylase such as inhibiting function of nickel ions on JMJD1A by replacing the ferrous iron in the catalytic centers [28]. Chronic exposure to nickel compounds has been connected to the increased risks of cancer, and alteration of histone modification may be one important factor [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that nickel increased H3K9 dimethylation by inhibiting the activity of Fe(II)-2-oxoglutarate-dependent histone H3K9 demethylase accompanied by inhibition of G9a methyltransferase [11, 32]. Further studies showed that histone-modifying enzymes, including acetyltransferases and methyltransferases, consumed the cellular intermediate metabolites acetyl-CoA and SAM as acetyl and methyl donors to promote histone acetylation and methylation, respectively [33].…”
Section: Discussionmentioning
confidence: 99%
“…Ni (II) has been found to inhibit demethylase activity of KDM3A (JMJD1A) in vitro , and in turn led to an accumulation of dimethylation at histone H3 lysine 9 (H3K9me2) (Chen et al 2010a). The same study also showed that the activity of DNA repair enzyme ABH2 was inhibited by Ni (II).…”
Section: Iron Homeostasis and Dioxygenase Activitymentioning
confidence: 99%
“…The same study also showed that the activity of DNA repair enzyme ABH2 was inhibited by Ni (II). Extended X-ray absorption fine structure showed that the best fit for iron binding ABH2 consists of five oxygen/nitrogen donor ligands of which two are histidine ligands; and when nickel binds to ABH2, the binding site is indistinguishable from the iron-binding site (Chen et al 2010a). Isothermal titration calorimetry analysis suggested that Ni (II) binds to ABH2 with higher affinity than Fe (II).…”
Section: Iron Homeostasis and Dioxygenase Activitymentioning
confidence: 99%
See 1 more Smart Citation